2019
DOI: 10.1038/s41598-019-51142-8
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the Gastrointestinal Microbiome Associated with Methamphetamine Use among Young Men who have Sex with Men

Abstract: Methamphetamine (MA) use is a major public health problem in the United States, especially among people living with HIV (PLWH). Many MA-induced neurotoxic effects are mediated by inflammation and gut microbiota may play a role in this process, yet the effects of MA on the microbiome have not been adequately explored. Therefore, we performed 16S rRNA gene sequencing on rectal swab samples from 381 men who have sex with men, 48% of whom were PLWH and 41% of whom used MA. We compared microbiome composition betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 62 publications
5
32
1
Order By: Relevance
“…The gut microbiome of HIV-infected individuals is characterized by enrichment of pro-inflammatory bacterial taxa such as Erysipelotrichaceae , Enterobacteriaceae , Desulfovibrionaceae , and Fusobacteria and depletion of anti-inflammatory taxa such as Lachnospiraceae , Ruminococceae , Bacteroides , and Rikenellaceae [ 6 , 17 , 20 , 28 , 29 ]. Ruminococcaceae family members are the main producers of short-chain fatty acids, which induce the differentiation of anti-inflammatory regulatory T cells [ 20 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gut microbiome of HIV-infected individuals is characterized by enrichment of pro-inflammatory bacterial taxa such as Erysipelotrichaceae , Enterobacteriaceae , Desulfovibrionaceae , and Fusobacteria and depletion of anti-inflammatory taxa such as Lachnospiraceae , Ruminococceae , Bacteroides , and Rikenellaceae [ 6 , 17 , 20 , 28 , 29 ]. Ruminococcaceae family members are the main producers of short-chain fatty acids, which induce the differentiation of anti-inflammatory regulatory T cells [ 20 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the abundance of Veillonellaceae was increased in chronically ART-naïve individuals compared to those with HIV seronegative status [ 19 ]. Moreover, Veillonella abundance was correlated with elevated levels of pro-inflammatory cytokines [ 28 ]. This could explain our finding that CD4/CD8 ratio was negatively correlated with the relative abundance of Veillonellaceae and positively associated with that of Succinivibrionaceae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that substances (e.g. methamphetamine) alter the microbiome, promote inflammation and may even mediate behavioural responses to drugs (71)(72)(73) . Taken together, FI may partially explain the impact of drug use on depression, with a cumulative impact over the life course.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined if the changes in gut microbiota induced by METH have a time effect. A cohort study with 381 men found that the use of METH led to an abnormal increase in proinflammatory gut microbiota, including some bacteria that produce neuroactive substances and those associated with HIV (Cook et al, 2019). Another research conducted by Xu examined the composition and diversity of gut microbiota in 45 patients with substance use disorders, indicating that there seems to be a substance-related change in gut microbiota (Xu et al, 2017).…”
Section: Prenatal Meth Exposure and Gut Microbiotamentioning
confidence: 99%